Human liver derived mesenchymal stromal cells ameliorate murine ischemia-induced inflammation through macrophage polarization - Liang, Yun; Ozdogan, Elif; Hansen, Michael J.; Tang, Hui; Saadiq, Ishran; Jordan, Kyra L.; Krier, James D.; Gandhi, Deep B.; Grande, Joseph P.; Lerman, Lilach O.; Taner, Timucin (Frontiers in Immunology, 2024)
The immunomodulatory properties of mesenchymal stromal cells (MSC) have been wellcharacterized in in-vitro and in-vivo models. We have previously shown that liver MSC (L-MSC) are superior inhibitors of T-cell activation/proliferation, NK cell cytolytic function, and macrophage activation compared to adipose (A-MSC) and bone marrow MSC (BM-MSC) invitro. To test these observations in-vivo, we infused these types of MSC into mice with unilateral renal artery stenosis (RAS), an established model of kidney inflammation. Unilateral RAS was induced via laparotomy in 11-week-old, male 129-S1 mice under general anesthesia. Control mice had sham operations. Human L-MSC, A-MSC, and BM-MSC (5x10 5 cells each) or PBS vehicle were injected intra-arterially 2 weeks after surgery. Kidney morphology was studied 2 weeks after infusion using micro-MRI imaging. Renal inflammation, apoptosis, fibrosis, and MSC retention were studied ex-vivo utilizing western blot, immunofluorescence, and immunohistological analyses. The stenotic kidney volume was smaller in all RAS mice, confirming significant injury, and was improved by infusion of all MSC types. All MSC-infused groups had lower levels of plasma renin and proteinuria compared to untreated RAS. Serum creatinine improved in mice treated with BM-and L-MSC. All types of MSC located to and were retained within the stenotic kidneys, but L-MSC retention was significantly higher than A-and BM-MSC. While all groups of MSC-treated mice displayed reduced overall inflammation and macrophage counts, L-MSC showed superior potency in-vivo at localizing to the site of inflammation and inducing M2 (reparative) macrophage polarization to reduce inflammatory changes. These in-vivo findings extend our in-vitro studies and suggest that L-MSC possess unique anti-inflammatory properties that may play a role in liver-induced tolerance and lend further support to their use as therapeutic agents for diseases with underlying inflammatory pathophysiology.